2010
DOI: 10.1111/j.1439-0272.2009.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anion channel blockers on l-arginine action in spermatozoa from asthenospermic men

Abstract: In earlier studies, we have established that l-arginine enhances motility and metabolic rate in spermatozoa of goat, bull and mouse. In the present study this work was extended to human sperm cells obtained from the semen samples of asthenospermic patients, which are characterised by low motility. The metabolic rate was followed by monitoring the glucose consumption (1-(13)C glucose as substrate) and the production of lactate in sperm cells, using (13)C NMR. The stimulatory effect of l-arginine was neutralised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Exogenous lactate and pyruvate play a vital role in stallion spermatozoa mitochondrial functionality and motility in a dose-dependent manner, as spermatozoa in these media operate at a very high level of bioenergetic capability due to their high rate of energy metabolism [ 26 ]. Supplementation with arginine stimulates metabolic the activity of spermatozoa in goats [ 31 ] and motility in rabbits [ 32 ] and human spermatozoa in vitro [ 33 34 ]. Arginine also serves as a source of NO, inducing capacitation and an acrosome reaction in bull spermatozoa [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous lactate and pyruvate play a vital role in stallion spermatozoa mitochondrial functionality and motility in a dose-dependent manner, as spermatozoa in these media operate at a very high level of bioenergetic capability due to their high rate of energy metabolism [ 26 ]. Supplementation with arginine stimulates metabolic the activity of spermatozoa in goats [ 31 ] and motility in rabbits [ 32 ] and human spermatozoa in vitro [ 33 34 ]. Arginine also serves as a source of NO, inducing capacitation and an acrosome reaction in bull spermatozoa [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that daily supplementation of arginine improves semen concentration and sperm motility (Holt & Albanese, 1944;Tanimura, 1967;Schachter et al, 1973;De-Aloysio et al, 1982;Scibona et al, 1994), while other authors did not succeed on showing any improvement in sperm characteristics or pregnancy rate (Mroueh, 1970;Pryor et al, 1978). There are also studies that have shown that arginine in excessive concentrations results in decrease on sperm function (Srivastava & Agarwal, 2010).…”
Section: Argininementioning
confidence: 97%
“…So, L-Arginine acts as free radical scavenger (reduce the harmful effect of lead) and prophylacting the hormonal and cellular damage in the testis of toxic rats (Table 2). It was pointed to L-Arginine administration as therapeutic or prophylactic beneficial, agent against the harmful effects of toxic compounds on testicular function of rats [39][40][41][42][43].…”
Section: Fig 2 Showed the Effect Of Administration Of 1% Lead Acetamentioning
confidence: 99%